(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Fuzzy logic is a powerful tool that can be used to solve real-world problems where data isn’t setand exact. It can be used as a very important platform for making decisions and other things that useartificial intelligence. A person can see how Fuzzy logic is used in a lot of different fields. Fuzzy logicprinciples play a big part because there are many levels of ambiguity and uncertainty when it comes tofiguring out what a person is sick with. The best and most accurate way to classify disease entities is touse language words, which are often vague and imprecise. When a doctor has a lot of experience, heusually prefers to talk about it in terms that are more normal for him and for the patient than to try to puthis knowledge into rigid rules that have simple premises, in general. Words like severe pain, forexample, are hard to write down and measure. Our research focuses on looking at how fuzzy models canhelp us solve problems for older people. People can use fuzzy logic principles to help them getestimates of what they know, which can then help them figure out what is going on. The goal of thisstudy is to use fuzzy logic principles to look at teenagers’ psychology in light of the Indiansituation.Elders have to deal with things like financial uncertainty, depression, instability, physicalweakness, social isolation, less strength, and more, to name a few. Abuse The elderly are forced to dohousehold chores and live in dungeon-like quarters by their daughters. Their land is taken over by theirchildren, they are left alone, and they are forced to leave their homes and leave their land to theirchildren. Rapid urbanisation and transition, the breakup of a traditional family structure, a high level ofschooling, job changes, and the move of young people to cities and abroad, as well as a lack of housingspace and a generational difference, are all reasons for people to not look after the old.